3p+6=-(1+4p)

Simple and best practice solution for 3p+6=-(1+4p) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3p+6=-(1+4p) equation:



3p+6=-(1+4p)
We move all terms to the left:
3p+6-(-(1+4p))=0
We add all the numbers together, and all the variables
3p-(-(4p+1))+6=0
We calculate terms in parentheses: -(-(4p+1)), so:
-(4p+1)
We get rid of parentheses
-4p-1
Back to the equation:
-(-4p-1)
We get rid of parentheses
3p+4p+1+6=0
We add all the numbers together, and all the variables
7p+7=0
We move all terms containing p to the left, all other terms to the right
7p=-7
p=-7/7
p=-1

See similar equations:

| 2+4r-10+6r=2(5r-4) | | -5x-20=50 | | 32+9x+1=13x-11 | | -7y+5=-6y+11 | | 5x+35=7x+15 | | 2x-12+2x+17+9x-7=180 | | 8x=(3x+5)+(6x-16) | | 7/3=x/1.5 | | (4x-13)=(3x+19)= | | x+x2=x(x+1) | | 3y–15=–21 | | 2x^2+3x=374 | | 15h-9=-4 | | 5(r-1)=2(r-4)=6 | | 4(3+6x)=10(4x-2) | | 55=-5(a-4) | | 6(y-1)-8=-3(-9y+2)-3y | | 2(x+5)-7=-1 | | 2x+26=134 | | 6-x=159 | | 7.3x-4=2-2.7x | | -3r+12-9r+8=-3(4r-7) | | 3z-(4-2z)=39 | | 4x–30+x+25=180 | | 800+20w=600+30w | | 2(4n-3)=9(n+2)+3n | | b-3b=-3 | | 5/a+3=8 | | 2.00+7.50=8.00+6.00x | | Y+46+y+12=y+10 | | -3(3n+6)=-63 | | 3x-(4-2x)=39 |

Equations solver categories